Lateral-torsional buckling of stainless steel I-beams in case of fire - Real, P. M. M. Vila (2012)
This work presents a numerical study of the behaviour of stainless steel I-beams subjected to lateral–torsional buckling in case of fire and compares the obtained results with the beam design curves of Eurocode 3. New formulae for lateral–torsional buckling, that approximate better the real behaviour of stainless steel structural elements in case of fire are proposed. These new formulae were based on numerical simulations using the program SAFIR, which was modified to take into account the material properties of the stainless steel.